2011
DOI: 10.1016/j.neures.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells as putative host cells for Streptococcus pneumoniae: Evidence of bacterial invasion via mannose receptor-mediated endocytosis

Abstract: Olfactory ensheathing cells (OECs) are a special glia that ensheath olfactory receptor axons that enter the brain via olfactory phila, thus, providing a potential route for access of pathogens. Streptococcus pneumoniae (Sp), that has a capsule rich in mannosyl residues, is the most common cause of rhinosinusitis that may evolve to meningitis. We have tested whether OECs in vitro express the mannose receptor (MR), and could internalize Sp via MR. Cultures were infected by a suspension of Sp (ATCC 49619), recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…The possible reasons for this were as follows. First, S. pneumoniae can identify the OEC surface mannose receptor and is located in OECs (Macedo-Ramos et al, 2011). OECs can also play an immune surveillance role and migrate (Williams et al, 2004) through the basement membrane (Windus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for this were as follows. First, S. pneumoniae can identify the OEC surface mannose receptor and is located in OECs (Macedo-Ramos et al, 2011). OECs can also play an immune surveillance role and migrate (Williams et al, 2004) through the basement membrane (Windus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also demonstrated that S. pneumoniae can invade olfactory ensheathing cells via mannose receptor-mediated endocytosis (334); however, the role of olfactory ensheathing cells in pneumococcal infection and the exact mode of transport of S. pneumoniae along the olfactory and/or trigeminal nerves have not yet been studied.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%
“…This result plus the concurrent infection of the nasopharynx and sinus tissue suggest a cascade of events that can lead to invasion and possibly that the severity of the sinus infection is a precursor to CNS invasion. This, along with recent evidence of the association and manipulation of the olfactory ensheathing cells by pneumococci (48,49), provides credence to the idea that the olfactory nerves are the portals of entry into the CNS.…”
Section: Discussionmentioning
confidence: 56%
“…We compared intravenous infection with D39.1, a strain with a pneumococcal serotype associated with bacteremia in animal models, to intranasal infection with EF3030. We took blood samples at 1,4,8,12,24,48,72, and 96 h postinfection. Our results indicated that intranasal infection with EF3030 does not produce significant bacteremia, even when blood is sampled at earlier time points during infection.…”
Section: Resultsmentioning
confidence: 99%